ANALISIS PENGARUH KUALITAS PELAYANAN DAN PROMOSI TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MODERASI - Erlinda Novita Putri; Edi Wibowo; Sumaryanto Sumaryanto (Universitas Slamet Riyadi, 2020)
The purpose of this study is to analyze the significance of effect service quality, promotion and satisfaction on consumer loyalty partially, to know the significance of effect of service quality and promotion on consumer loyalty which is moderated by customer satisfaction. This type of research is a survey of consumers of SFA Steak & Resto Karanganyar. A sample of 100 consumers with purposive sampling technique. Data collection techniques used questionnaire and literature study. The data analysis technique used multiple linear regression and absolute difference test. The results showed that service quality, promotion and customer satisfaction partially have a significant effect on consumer loyalty of SFA Steak & Resto in Karanganyar. Consumer satisfaction moderates the effect of service quality on consumer loyalty SFA Steak & Resto in Karanganyar. Consumer satisfaction does not moderate the effect of promotion on consumer loyalty at SFA Steak & Resto in Karanganyar.